Body weight status, eating behavior, sensitivity to reward/punishment, and gender: relationships and interdependencies - Dietrich, Anja; Federbusch, Martin; Grellmann, Claudia; Villringer, Arno; Horstmann, Annette (Frontiers in Psychology, 2014)
Behavioral and personality characteristics are factors that may jointly regulate body weight. This study explored the relationship between body mass index (BMI) and self-reported behavioral and personality measures. These measures included eating behavior (based on the Three-Factor Eating Questionnaire- TFEQ) (Stunkard and Messick, 1985), sensitivity to reward and punishment (based on the BIS/BAS Scales) (Carver and White, 1994) and self-reported impulsivity (based on the Barratt Impulsiveness Scale-11) (Patton et al., 1995). We found an inverted U-shaped relationship between restrained eating and BMI. This relationship was moderated by the level of disinhibited eating. Independent of eating behavior, BIS and BAS responsiveness were associated with BMI in a gender-specific manner with negative relationships for men and positive relationships for women. Together, eating behavior and BIS/BAS responsiveness accounted for a substantial proportion of BMI variance (men: ~25%, women: ~32%). A direct relationship between self-reported impulsivity and BMI was not observed. In summary, our results demonstrate a system of linear and non-linear relationships between the investigated factors and BMI. Moreover, body weight status was not only associated with eating behavior (cognitive restraint and disinhibition), but also with personality factors not inherently related to an eating context (BIS/BAS). Importantly, these relationships differ between men and women.